Comparative analysis of modern led lamps - Volkova, I. (ТДАТУ, 2018)
EN: The most popular types of LED lamps among local people are considered in this article. The most economical type in everyday life is presented in this research. UK: У статті розглядаються найпопулярніші види світлодіодних ламп серед місцевого населення. Найбільш економний типу повсякденному житті представлений у цьому дослідженні.
Keywords: світлодіодні лампи; LED lamps; electricity prices; economical type of LEDs